Intrapatient comparisons of efficacy in a single-arm trial of entrectinib in tumour-agnostic indications - Krebs, M.G. (ESMO Open, 2021)
BACKGROUND: Entrectinib is a tropomyosin receptor kinase inhibitor approved for the treatment of neurotrophic tyrosine receptor kinase (NTRK) fusion-positive solid tumours based on single-arm trials. Traditional randomised clinical trials in rare cancers are not feasible; we conducted an intrapatient analysis to evaluate the clinical benefit of entrectinib versus prior standard-of-care systemic therapies. METHODS: Patients with locally advanced/metastatic NTRK fusion-positive tumours enrolled in the global phase II, single-arm STARTRK-2 trial were grouped according to prior systemic therapy and response. The key analysis used growth modulation index [GMI; ratio of progression-free survival (PFS) on entrectinib to time to discontinuation (TTD) on the most recent prior therapy]; ratio ≥1.3 indicated clinically meaningful efficacy. Additional analyses investigated TTD and objective response rate (ORR) for entrectinib and prior therapies. RESULTS: Seventy-one patients were included; 51 received prior systemic therapy. In 38 patients who progressed on prior therapy, ORR was 60.5% (23/38) with entrectinib and 15.8% (6/38) with the most recent prior therapy. Median PFS [11.2 months; 95% confidence interval (CI) 6.7–not estimable] for entrectinib exceeded median TTD (2.9 months; 95% CI 2.0-4.9) for most recent prior therapy. From the intrapatient analysis of GMI, 65.8% had a ratio ≥1.3 and median GMI was 2.53. Consistent results were observed at more stringent GMI thresholds; 60.5% of patients had GMI ≥1.5 or ≥1.8 and 57.9% had GMI ≥2.0. CONCLUSIONS: ORR was high and PFS was longer on entrectinib versus TTD on prior therapy. Furthermore, 65.8% of patients experienced clinically meaningful benefit based on GMI. This intrapatient analysis demonstrates comparative effectiveness of entrectinib in a rare, heterogeneous adult population.